Achieving Efficient and Stable Perovskite Solar Cells in Ambient Air Through Non‐Halide Engineering. Issue 42 (10th October 2021) - Wang, Zhen; Jin, Junjun; Zheng, Yapeng; Zhang, Xiang; Zhu, Zhenkun; Zhou, Yuan; Cui, Xiaxia; Li, Jinhua; Shang, Minghui; Zhao, Xingzhong; Liu, Sheng; Tai, Qidong
Abstract: The realization of highly efficient perovskite solar cells (PSCs) in ambient air is considered to be advantageous for low‐cost commercial manufacturing. However, it is fundamentally difficult to achieve comparable device performance to that obtained in an inert atmosphere, especially when the ambient humidity is high. Here, an effective precursor engineering that simultaneously employs non‐halide lead acetate and lead thiocyanate lead sources for fabricating high‐quality methylammonium lead iodide perovskite films in ambient air with enhanced moisture tolerance, is reported. The presence of Ac – and SCN – ions not only enables the facile formation of homogeneous and highly crystalized perovskite films, but also directs the uniform growth of the crystals along the (110) direction. Accordingly, a 20.55% efficiency is demonstrated, one of the best results for air‐processed MAPbI3 PSCs, which is also the highest value achieved with non‐halide lead sources. Furthermore, the unencapsulated device shows fivefold prolonged air stability (3600 h) compared to the conventional PbI2 ‐based PSC. Together with the use of non‐toxic antisolvent, this strategy is fully compatible with ambient air operation and thus of great potential for practical applications. Abstract : Herein, lead acetate and lead thiocyanate are explored as dual lead sources to prepare high‐quality methylammonium lead iodide perovskite films in ambient air through an eco‐friendly way, which results in unprecedented efficiency for perovskite solar cells prepared from non‐halide lead sources. In addition, the device also shows excellent air stability.